A 2D strip ionization chamber array with high spatiotemporal resolution for proton pencil beam scanning FLASH radiotherapy. Issue 8 (30th May 2022) - Yang, Yunjie; Shi, Chengyu; Chen, Chin‐Cheng; Tsai, Pingfang; Kang, Minglei; Huang, Sheng; Lin, Chih‐Hsun; Chang, Fu‐Xiong; Chhabra, Arpit M.; Choi, J. Isabelle; Tome, Wolfgang A.; Simone, Charles B.; et al.
Abstract: Purpose: Experimental measurements of two‐dimensional (2D) dose rate distributions in proton pencil beam scanning (PBS) FLASH radiation therapy (RT) are currently lacking. In this study, we characterize a newly designed 2D strip‐segmented ionization chamber array (SICA) with high spatial and temporal resolution and demonstrate its applications in a modern proton PBS delivery system at both conventional and ultrahigh dose rates. Methods: A dedicated research beamline of the Varian ProBeam system was employed to deliver a 250‐MeV proton PBS beam with nozzle currents up to 215 nA. In the research and clinical beamlines, the spatial, temporal, and dosimetric performances of the SICA were characterized and compared with measurements using parallel‐plate ion chambers (IBA PPC05 and PTW Advanced Markus chamber), a 2D scintillator camera (IBA Lynx), Gafchromic films (EBT‐XD), and a Faraday cup. A novel reconstruction approach was proposed to enable the measurement of 2D dose and dose rate distributions using such a strip‐type detector. Results: The SICA demonstrated a position accuracy of 0.12 ± 0.02 mm at a 20‐kHz sampling rate (50 μs per event) and a linearity of R 2  > 0.99 for both dose and dose rate with nozzle beam currents ranging from 1 to 215 nA. The 2D dose comparison to the film measurement resulted in a gamma passing rate of 99.8% (2 mm/2%). A measurement‐based proton PBS 2D FLASH dose rate distribution was compared to simulation results and showed a gamma passing rate of 97.3% (2 mm/2%). Conclusions: The newly designed SICA demonstrated excellent spatial, temporal, and dosimetric performances and is well suited for commissioning, quality assurance, and a wide range of clinical applications in proton PBS clinical and FLASH‐RT.